SEPARATION OF 3-MCPD AND GLYCIDYL ESTERS FROM PALM OIL USING ADSORBENTS BASED ON A MIXTURE OF ZEOLITE AND ACTIVATED CARBON FROM COCONUT SHELLS - Gabryella Lukrina, Bellentz
Separation of 3-MCPD and Glycidyl Esters from Palm Oil Using Adsorbents Based on a Mixture of Zeolite and Activated Carbon from Coconut Shells. Crude palm oil (CPO) is unrefined palm oil obtained from the pressing process of oil palm fruits. Palm oil is a widely consumed oil and is used extensively in the food industry. The compounds 3-monochloropropane-1,2-diol (3-MCPD) and glycidyl esters (GEs) are known process contaminants that are found to be relatively abundant in refined palm oil compared to other refined vegetable oils, such as soybean, canola, and sunflower. These contaminants are mostly formed during the crude palm oil (CPO) refining process due to the reaction between lipids-such as triacylglycerol (TAG) and diacylglycerol (DAG)-with chlorides during high-temperature processing. This study aims to reduce the concentration of 3-MCPD and glycidyl esters in RBDPO by adsorption method using a mixture of activated carbon and zeolite. Activated carbon and zeolite were first activated using HNO3 before being used as adsorbents. Adsorption was conducted to adsorb 3-MCPD in RBDPO with 3% w/w adsorbent concentration. The adsorbent preparation method was carried out by mixing activated carbon and zeolite in the ratio of 1:1, 2:1, and 1:2, based on the arrangement of a certain mixing mechanism. The adsorption process of 3-MCPD and GE in RBDPO was carried out at 45 oC with a batch system. Based on the results, the variation with the mixing mechanism arrangement of activated carbon and zeolite added simultaneously with an adsorbent ratio of 1:1 resulted in the best %removal for 3-MCPD and GE. Using statistical analysis, it was found that the main factors that significantly influenced the adsorption process of 3-MCPD and GE were adsorption time and mixing mechanism arrangement.